Competence-based curriculum development for general practice in Germany: a stepwise peer-based approach instead of reinventing the wheel - Steinhäuser, Jost; Chenot, Jean-François; Roos, Marco; Ledig, Thomas; Joos, Stefanie (BMC Research Notes, 2013)
Improving postgraduate medical training is one important step to attract more medical students into general practice. Keeping pace with international developments moving to competence-based curricula for general practice training, the aim of this project was to develop and implement such a curriculum in Germany.